Numerical simulation of a sonic-underexpanded jet impinging on a partially covered cylindrical Hartmann whistle. (August 2018) - Samanta, Arnab; Narayanan, S; Kumar Jha, Shailesh; Narayan, Ashish
The present study numerically investigates the effect of a partially covered cylindrical shield on the flow/shock oscillation characteristics of a Hartmann whistle when the pulsating jet exits through the two small openings, (a) close to the cavity inlet, and (b) away from the cavity inlet, of the cylindrical shield. The relevant parameters that modify the flow/shock oscillations of the Hartmann whistle are the stand-off distance, nozzle pressure ratio, cavity length, cavity shield, jet diameter, etc. The pulsating nature of flow in a partially shielded Hartmann whistle is investigated for various stand-off distances to understand its effect in achieving effective flow control. The velocity vectors indicate that the partly shielded Hartmann whistle operates in the jet regurgitant mode with different regurgitant phases. It also shows that some amount of the jet near the cavity inlet gets diverted towards the shield and gets attached to it, whereas some exits out through the two shield openings which can be injected into the flow to be controlled. The Mach number contours indicate the flow deceleration/reacceleration zones, shock-cell structures as well as fluid column oscillations in shock-cells/cavity regions. The present study reveals that the stand-off distance and the jet diameter are the crucial parameters, which control the oscillation mechanisms in a partially covered Hartmann whistle for achieving effective flow control. Thus, this paper sufficiently demonstrates the role of stand-off distances, openings in the shield as well as jet diameter in modifying the flow/shock oscillation characteristics of a partially shielded Hartmann whistle in achieving the finest flow control.